Can 'English Premier League' funding for PE and school sport achieve its aims?. (3rd March 2016) - Zwolinsky, Stephen; McKenna, Jim; Parnell, Daniel; Pringle, Andy
Abstract : There are a number of assertions being made for a £10 m investment by the English Premier League for primary school sport. For example, it is claimed that Physical Education plus school sport can improve cognitive functioning, concentration, behaviour, educational attainment and overall physical health. However, far from being sufficient in helping to achieve these benefits and sustain long-term activity participation, for some children, Physical Education and competitive sport may actually be counterproductive. In some instances, it may switch them off from activity altogether. Therefore, we need to understand more about which elements of this scheme work, who they work for and which circumstances they work in. Fundamentally, this will only be achieved through hard evidence and robust evaluation.